2002
DOI: 10.1074/jbc.c200314200
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 3,4,5,6-Tetrakisphosphate Inhibits Insulin Granule Acidification and Fusogenic Potential

Abstract: ClC Cl؊ channels in endosomes, synaptosomes, lysosomes, and ␤-cell insulin granules provide charge neu- . We now ascribe just such a regulatory function to the increases in cellular levels of inositol 3,4,5,6-tetrakisphosphate (Ins(3,4,5,6)P 4 ) that inevitably accompany activation of the ubiquitous Ins(1,4,5)P 3 signaling pathway. We used confocal imaging to record insulin granule acidification in single mouse pancreatic ␤-cells. Granule acidification was reduced by perfusion of single cells with 10 M Ins(3,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The regulation of organelle pH by activation of the NAADP receptor on the vesicle membrane poses exciting questions relating not just to sea urchin biology but also to mammalian biology. Certainly, key enzymes in the lumen of egg vesicles are regulated by pH changes at fertilization (14,38), but in the acidic organelles of mammalian cells, luminal pH influences processes as diverse as secretory vesicle fusion (39), autophagy (40), and proteolysis (41). Our results may have far-reaching implications for NAADP regulating various cellular pathways via pH and not just by Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 89%
“…The regulation of organelle pH by activation of the NAADP receptor on the vesicle membrane poses exciting questions relating not just to sea urchin biology but also to mammalian biology. Certainly, key enzymes in the lumen of egg vesicles are regulated by pH changes at fertilization (14,38), but in the acidic organelles of mammalian cells, luminal pH influences processes as diverse as secretory vesicle fusion (39), autophagy (40), and proteolysis (41). Our results may have far-reaching implications for NAADP regulating various cellular pathways via pH and not just by Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 89%
“…This acidification is considered to be an important step to produce fusion-competent vesicles in the final stages of exocytosis (Hou et al, 2009). This means that Ins(3,4,5,6)P 4 acts to inhibit acidification and, thus, exocytosis (Renström et al, 2002). Two studies showing the importance of the ClC-3 channel for insulin exocytosis were published in Cell Metabolism (Deriy et al, 2009;Li et al, 2009).…”
Section: Higher Inositol Polyphosphatesmentioning
confidence: 99%
“…In this way Ins (3,4,5,6)P 4 regulates a range of biological processes, including salt and fluid secretion, neurotransmission, and insulin secretion from pancreatic ␤-cells (8,(11)(12)(13). Recently it was shown that changes in ITPK1 * This work was based on experiments conducted at beamlines 5.0.3 and 5.0.2 of the Advanced Light Source (ALS).…”
mentioning
confidence: 99%